THE RELATIONSHIP BETWEEN PERFORMANCE OF THE ADMINISTRATIVE SYSTEM AND NATIONAL AUTHORITY OF GOVERNMENTS: AN ISLAMIC POINT OF VIEW - Mahtab Jafari (Сучасний стан наукових досліджень та технологій в промисловості, 2018)
Each government consists of two dimensions: 1) a structural dimension that involves policy- and decision-making bodies and, 2) a functional dimension that is a set of government institutions and administrations. Also, the national authority in a country is an outcome of three components, including legitimacy, acceptance, and efficiency of its government. The authority of governments is not merely limited to their structural legitimacy and acceptance; but, their functional dimension and the performance of their administrations also play a crucial role in building and strengthening their legitimacy. Therefore, the aim of the present study is to investigate how the administrative system of a government affects its national authority, with an emphasis on the Islamic point of view. To do this, this research has been carried out within the framework of theoretical research with a practical purpose.  The research method of the current study was the descriptive and analytical. In this study, the relationship between two variables – namely, “administrative system” and “national authority” – has been investigated within the framework of the causal research. Due to the theoretical nature of this study, the resources used mostly include documents and library sources. The results of this study indicate that there is a direct and causal relationship between the national authority of governments (effect) and the performance of their administrative system (cause). Also, this relationship reveals how the administrative system affects national authority.